TEKNIK DASAR SERVIS, PUKULAN FOREHAND DAN BACKHAND BULUTANGKIS PADA SISWA KELAS VIIA DI SMP - Setiawati, Hernita; Simanjuntak, Victor; Atiq, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
Â Abstrak: Penelitian ini tujuan dalam penelitian ini adalah untuk mengetahui teknik dasar permainan bulutangkis pada siswa kelas VIIASMP Negeri 11 Pontianak. Menggunakan metode deskriptif kuantitatif dengan bentuk survei. Bentuk sampel dalam penelitian ini berjumlah 35 orang. Diketahui hasil penelitian adalah servis pendek kategori sangat baik 8,6 % berjumlah 3 orang, kategori baikÂ 45,7 % berjumlah 16 orang, kategori cukup 17,1 % berjumlah 6 orang, kategori kurang 20% berjumlah 7 orang dan kategori sangat kurang 5,7 % berjumlah 2 orang. Servis panjang, kategori sangat baik 28,6 % berjumlah 10 orang, kategori baik 31,4 % berjumlah 11 orang, katgori cukup 11,4 % berjumlah 4 orang, kategori kurang 14,3 % berjumlah 5 orang dan kategori kurang sekali 11,4 % berjumlah 4 orang. Forehand, kategori sangat baik 40 % berjumlah 14 orang, kategori baik 22,8 % berjumlah 9 orang, kategori cukup 8,57 % berjumlah 3 orang, kategori kurang 23 % berjumlah 9 orang dan kategori kurang sekali 0,28 % berjumlah 1 orang. Backhand, kategori sangat baik 11,4 % berjumlah 4 orang, kategori baik 37,1 % berjumlah 13 orang, kategori cukup 25,7 % berjumlah 9 orang, kategori kurang 14,3 % berjumlah 5 orang dan kategori sangat kurang 11,4 % berjumlah 4 orang. Kata Kunci : Teknik Dasar,Servis, Pukulan Forehand dan Backhand, Bulutangkis Abstract: This research purpose of this research is to know the basic techniques of the game of badminton on State 11 grade students VIIASMP Pontianak. Using quantitative descriptive method with the survey form. The form of the sample in this study amounted to 35 people. Known research results are very good short service category numbered 3 8.6%, both categories of 16 people 45.7%, 17.1% fair category amounted to 6 persons, about 20% category amounted to 7 people and very poor category 5, 7% amounting to 2 people. Service length, very good category 28.6% were 10 people, both categories totaled 31.4% 11, 11.4% katgori enough amounted to 4 people, 14.3% less category 5 and category totaled approximately once 11.4 % consists of 4 people. Forehand, very good 40% category amounted to 14 people, both categories totaled 22.8% 9 people, enough categories totaled 8.57% 3, less 23% category amounted to 9 people and less categories once amounted to 0.28% 1. Backhand, very good category consists of 4 people 11.4%, 37.1% both categories totaled 13 people, enough categories totaled 9 25.7%, 14.3% less category amounted to 5 people and very poor category 11.4% amounted to 4 people. Key words: Basic Techniques, Service, Forehand and Backhand Blow, Badminton